Detection of Anti-Echinococcus granulosus Antibodies in Humans: An Update from Pakistan - Khan, Huma; Ahmed, Haroon; Afzal, Muhammad Sohail; Awan, Usman Ayub; Khurram, Muhammad; Simsek, Sami; Cao, Jianping (Mdpi, 2022)
Human cystic echinococcosis (CE) is a zoonotic disease caused by the larval stage of Echinococcus granulosus sensu lato that causes economic losses by affecting livestock and also poses a public health threat worldwide. The present study is the first retrospective report on the seroprevalence of anti-E. granulosus antibodies in humans in Pakistan. The study used data from 93 blood analysis reports of patients suspected of having CE from different medical centers in Lahore, Pakistan. Out of 93 sera samples, 20 (21.5%) were seropositive, and higher seropositivity (17.2%) was recorded with the indirect hemagglutination test (IHA) than with enzyme-linked immunosorbent assay (ELISA). The findings indicated that age, gender, and year had no significant relationship with the seropositivity of CE. The current study provides directions towards the management of the disease in the near future in Pakistan.
Keywords: cystic echinococcosis; hydatid cysts; seropositivity; ELISA; IHA; Pakistan; hydatic cysts